A motion-based visual interface for 3D visualization and robotic control applications - Hussaini, S; Wooi-Boon Goh (2010 11th International Conference on Control Automation Robotics and Vision, 2010)
The exploratory visualization of 3D data sets or multiple axis motion control of a monitoring camera mounted on a six-axis robot often require the user to control the viewing orientation and position of a camera view within a 3D space. This paper describes the design of an inertial motion sensing system, which uses only accelerometers to provide interactive 3D control of both orientation and position in such systems. We describe the interaction design strategies for exploratory visualization of 3D data using the proposed input device, which is mounted beneath a portable display. Experiments on the use of the proposed device suggest that with some training, the users are able to improve the speed with which they can navigate the orientation and position of a virtual camera to a desired target view in the 3D visual space.